The Impact of a Phytobiotic Mixture on Broiler Chicken Health and Meat Safety - Hubert Iwiński; Karolina A. Chodkowska; Kamil Drabik; Justyna Batkowska; Małgorzata Karwowska; Piotr Kuropka; Adam Szumowski; Antoni Szumny; Henryk Różański (Animals, 2023)
The purpose of the study was to assess the effects of different doses of a phytobiotic mixture on selected production parameters and meat quality and to assess the residue of the preparation in tissues and the possible toxic effects in broiler chickens. Broiler chicks aged 160 days, divided into four equal groups, were supplemented with the phytobiotic mixture at different doses, D1—0.5 mL/L, D2—1 mL/L, and D3—2 mL/L, four times during a 42-day trial. There were no statistically significant differences in weight gain per week of life and mortality in the birds. The study also demonstrated that the use of the mixture of phytobiotics had no significant effect on colour, pH, WHC, and natural leakage. However, a beneficial effect of the additive was found in the group treated with a dose of 1 mL/L, where less thermal leakage from the meat was demonstrated. Furthermore, significant differences in the change in thigh muscle tenderness were also observed. In the histopathological analysis of the liver no significant differences were observed. In addition, no residues of the mixture or its metabolites were found in the tissues analysed. In conclusion, the proposed scheme of administration of the phytobiotic additive, regardless of the dose, does not cause pathological changes in organs and does not carry the risk of residues of the product in tissues intended for human consumption.